Integrated Analysis of Summary Statistics to Identify Pleiotropic Genes and Pathways for the Comorbidity of Schizophrenia and Cardiometabolic Disease - Liu, Hao; Sun, Yang; Zhang, Xinxin; Li, Shiyang; Hu, Dong; Xiao, Lei; Chen, Yanghui; He, Lin; Wang, Dao Wen (Frontiers in Psychiatry, 2020)
Genome-wide association studies (GWAS) have identified abundant risk loci associated with schizophrenia (SCZ), cardiovascular disease and metabolic diseases (including body mass index, type 2 diabetes, low- and high-density lipoprotein, total cholesterol and triglycerides). Although recent studies have suggested shared genetic risk between these disorders, the common risk genes and biological pathways shared between them are still vague. Here we integrated comprehensive multi-dimensional data from GWAS, expression quantitative trait loci (eQTL) and gene set database to systematically identify potential pleiotropic genes and biological pathways shared between SCZ and cardiometabolic disease (CMD). By integrating the results from different approaches including FUMA, Sherlock, SMR, UTMOST, FOCUS and DEPICT, we revealed 21 promising causal genes that are likely to be shared between SCZ and CMD. These genes include VRK2, SLC39A8, NT5C2, AMBRA1, ARL6IP4, OGFOD2, PITPNM2, CDK2AP1, C12orf65, ABCB9, SETD8, MPHOSPH9, FES, FURIN, INO80E, YPEL3, MAPK3, SREBF1, TOM1L2, GATAD2A and TM6SF2. In addition, we also performed the gene-set enrichment analysis using the software of GSA-SNP2 and MAGMA with GWAS summary statistics and identified three biological pathways (MAPK_TRK signaling, growth hormone signaling, and regulation of insulin secretion) shared between them. Our study provides insights into the pleiotropic genes and biological pathways underlying mechanisms for the comorbidity of SCZ and CMD. However, further genetic and functional studies are required to validate the role of these promising candidate genes and pathways in the etiology of the comorbidity of SCZ and CMD, which should provide potential targets for future diagnostics and therapeutics.